ICE manual of construction materials - Forde, Mike, Prof (Thomas Telford, 2009)
This essential two volume work is a single stop, comprehensive reference for practicing engineers. It covers each of the key materials used in construction, detailing their properties and application in a civil and structural engineering context, and referencing the most up-to-date standards governing their use.